2020
DOI: 10.1007/s13753-020-00313-7
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Policy, Operations, and Research Uses for a Building Inventory in an Earthquake-Prone City

Abstract: After the 2016 New Zealand Kaikoura Earthquake, the absence of information about the state of buildings in Wellington proved to be a source of significant policy uncertainty. Authorities did not know what damages to expect and therefore how to react, and policies needed to be formulated without a clear quantification of the risks. Moreover, without detailed knowledge of the existing buildings, it was difficult to assess what the available legal and regulatory tools can achieve and choose among them. We describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Regional seismic data collection involves data privacy, data availability and data communication concerns imposed by data protection legislations ( Enachescu, 2007 ; Elwood et al, 2020 ). To mitigate these challenges the concept of FL has been proposed ( Aledhari et al, 2020 ).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Regional seismic data collection involves data privacy, data availability and data communication concerns imposed by data protection legislations ( Enachescu, 2007 ; Elwood et al, 2020 ). To mitigate these challenges the concept of FL has been proposed ( Aledhari et al, 2020 ).…”
Section: Related Workmentioning
confidence: 99%
“…It also evoked major issues about data privacy, data availability, data security, data protection, and data reliability. Seismic data is one of the most valuable resources, and agencies usually avoid data sharing due to data protection legislations about the sensitive nature of data ( Elwood et al, 2020 ; Enachescu, 2007 ). International agencies provide open access satellite datasets with reasonable accuracy but its high cost and the issue of indigenous knowledge (IK) poses a great challenge in terms of data capturing, storage and distribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…reached similar conclusions and found that aftershock effects are heavily influenced by the detailing of RC components. Through review of numerous experimental studies on components, Elwood et al 21 . showed that the deformation capacity of ductile (modern detailing) RC frame components is largely unaffected by cyclic loading that does not exceed 2% drift.…”
Section: Related Previous Workmentioning
confidence: 99%
“…Reinforced concrete was used in New Zealand from the early 1900s (Reed, Schoonees, and Salmond, 2008), but became more prevalent following the decline of unreinforced masonry in the 1930s, after many such buildings collapsed in the Hawke's Bay earthquake of 1931. Buildings with precast floors also comprise a large proportion of commercial building stock in Wellington, although some of them have been converted more recently from commercial to residential use (Elwood et al, 2020).…”
Section: Wellington's Existing Building Stock and Its Retrofittingmentioning
confidence: 99%